Huang-Lian Jie-Du decoction: a review on phytochemical, pharmacological and pharmacokinetic investigations - Yiyu Qi; Qichun Zhang; Huaxu Zhu (BMC, 2019)
Abstract Huang-Lian Jie-Du decoction (HLJDD), a famous traditional Chinese prescription constituted by Rhizoma Coptidis, Radix Scutellariae, Cortex Phellodendri and Fructus Gradeniae, has notable characteristics of dissipating heat and detoxification, interfering with tumors, hepatic diseases, metabolic disorders, inflammatory or allergic processes, cerebral diseases and microbial infections. Based on the wide clinical applications, accumulating investigations about HLJDD focused on several aspects: (1) chemical analysis to explore the underlying substrates responsible for the therapeutic effects; (2) further determination of pharmacological actions and the possible mechanisms of the whole prescription and of those representative ingredients to provide scientific evidence for traditional clinical applications and to demonstrate the intriguing molecular targets for specific pathological processes; (3) pharmacokinetic feature studies of single or all components of HLJDD to reveal the chemical basis and synergistic actions contributing to the pharmacological and clinically therapeutic effects. In this review, we summarized the main achievements of phytochemical, pharmacological and pharmacokinetic profiles of HLJDD and its herbal or pharmacologically active chemicals, as well as our understanding which further reveals the significance of HLJDD clinically.